Optical confinement achieved in zinc oxide modified by energetic silicon ions beams. (1st September 2017) - Ming, X.; Lu, F.; Zhang, Y.; Zhang, F.; Ma, C.; Fan, R.; Xu, B.
Highlights: Optical confinement is demonstrated in zinc oxide by silicon ions irradiation. Waveguide was formed at near surface region in as-irradiated zinc oxide samples. Waveguide properties and refractive index profile were studied and reconstructed. Abstract: Optical confinement was achieved in zinc oxide by silicon ions irradiation. Waveguide effects were found in all the irradiated samples. The optical properties and the field intensity distribution of the propagation mode, as well as the refractive index profile in the irradiated waveguide were studied and reconstructed accordingly. Achievement of optical waveguide structure in zinc oxide by silicon ions irradiation makes it possible to expand its application in modern optics and optical telecommunications in an attempt to control the propagation of light and to enhance the optical efficiency.